2017
DOI: 10.1094/cchem-02-17-0037-r
|View full text |Cite
|
Sign up to set email alerts
|

Folate Stability in Folic Acid Enriched Corn Masa Flour, Tortillas, and Tortilla Chips over the Expected Shelf Life

Abstract: Neural tube defects occur at higher rates in Hispanic populations in the United States. Such populations would benefit from folic acid fortification of corn masa flour (CMF). This study evaluated folate stability in fortified CMFs and tortillas and tortilla chips made therefrom. There was no significant loss of folate during the six‐month shelf life of fortified tortilla CMF and tortilla chip CMF. There was a 13% loss (P < 0.05) of folate during tortilla baking and no loss during tortilla chip frying. Both tor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…Swindler (2013) also reported 24% loss of native folate in unfortified wheat flour after six months of storage at room temperature in sealed cans, but no significant loss of added folic acid in enriched wheat flour stored over the same time in the same conditions. Phillips et al (2017) also showed that folic acid was stable in well-packaged fortified flours: they measured the folic acid content of fortified corn masa flour stored at 22 °C and 65% RH for up to six months in kraft plastic-lined bags [ i.e . multilayer packaging made up of brown paper and plastic], and did not observe any significant differences across the six-month shelf life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Swindler (2013) also reported 24% loss of native folate in unfortified wheat flour after six months of storage at room temperature in sealed cans, but no significant loss of added folic acid in enriched wheat flour stored over the same time in the same conditions. Phillips et al (2017) also showed that folic acid was stable in well-packaged fortified flours: they measured the folic acid content of fortified corn masa flour stored at 22 °C and 65% RH for up to six months in kraft plastic-lined bags [ i.e . multilayer packaging made up of brown paper and plastic], and did not observe any significant differences across the six-month shelf life.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out in the 1970s on the folic acid retention in fortified cereal-based products during storage and baking suggested that there was little loss (Berry, Bailey, Mulinare, Bower, & Dary, 2010), but the packaging and storage conditions were not always fully described. Recently, Phillips, Pike, Eggett, and Dunn (2017) did not report any significant loss of added folic acid in corn masa flour for up to six month of storage, but the flour was well-packaged and stored at 22 °C and 65% relative humidity. However, the influence of packaging on the stability of fortified flours stored in ‘tropical conditions’ ( i.e .…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have pointed out that folate had a small amount of loss in the process of baking and storage [34,35]. Similarly, SCR lost parts of folate during cake baking.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of folic acid stability in preparations developed with enriched flours was also studied by Phillips [27]. When evaluating tortillas and chip tortillas made from fortified cornmeal, the author found a 13% loss of folic acid.…”
Section: Plos Onementioning
confidence: 99%